Clay‐sized Hf‐Nd‐Sr isotopic composition of Mongolian dust as a fingerprint for regional to hemispherical transport. Issue 13 (14th July 2015) - Zhao, Wancang; Sun, Youbin; Balsam, William; Zeng, Lin; Lu, Huayu; Otgonbayar, Khureldavaa; Ji, Junfeng
Abstract Hf‐Nd‐Sr isotopic fingerprinting has been employed as a powerful method for distinguishing dust sources. However, the Hf and Sr isotopic compositions of dust are highly dependent on particle size to accurately identify dust provenance. Here we compare the Hf‐Nd‐Sr isotopic compositions of clay‐sized fractions from dust sources (the Mongolian Plateau) to sinks (Beijing and Greenland). Our results document that clay‐sized Hf‐Nd‐Sr isotopic compositions of Mongolian dust are controlled by two isotopic/geochemical provinces: Southern Mongolian Gobi (SMG) and Northern Mongolian Plateau (NMP). Our data indicate that the SMG is potentially an important dust source to the loess in Beijing and Hulun Buir and could be a contributing source of dust to Greenland, whereas the NMP contributes little dust to the Chinese loess and the Greenland. Furthermore, we demonstrate that the deserts of northwest China are one of the main dust contributors to Beijing and Greenland, but not to Hulun Buir.